فلسفة التاريخ عند عبد الرحمن ابن خلدون - ميسوم, بلقاسم (Sciences de l'Homme et de la Société, 2017)
أعطى عبد الرحمن ابن خلدون (1332-1406) فهما نقديا للتاريخ ومعه ظهر الظاهر والباطن للتاريخ،فلم تصبح الأحداث–حسبه- مجرد سرد،بل نظر ونقد وتعليل،واشتملت مقدمة"كتابه"في التاريخ وضع علم جديد في الحضارة البشرية  بحيث أنه عرض لنا خلاصة لجميع معارف العصور السالفة،في مختلف الميادين ،وهو بذلك أعطى فكرة جلية عن المستوى الذي بلغه العلم في العالم الإسلامي في بداية القرن الخامس عشر الميلادي،وهو واحد من أبرز علماء الإسلام،زد على ذلك أن ابن خلدون يمثل من ناحية أصله وسيرة حياته مزيجا هاما لحضارة ذلك العصر،مما انعكس على طبيعة تدوين "المقدمة" و"ديوان المبتدأ والخبر..."،ويطرح هذا المقال الإشكالية التالية:إلى أي حد تمكن ابن خلدون من عرض فهم فلسفي للتاريخ؟ Abstract :                 Ibn-Khadoun(1332-1406)  had given a new critical comprehension to history. With Ibn-Kaldoun, all the hidden and innermost aspects of history emerged and came to surface.Tevents are no longer just a subject of narration,but rather : critiqism and reasoning.his (Introduction ) “EL-MOUKADIMA”.had included the basis of a new science of the human civilization. However, he had exposed to us a hole summary of the human knowledge of the past history in all domains. Doing so, he had shown a new clear idea of the level of sciences that the moslims had reached at the beginning of the fifteenth century. In fact, he was one of the most remarkable moslim scientists. In addition to that, his origins and his way of life reveal that he was a melting pot of the civilization of that time. All that, had influenced enormously the way he had approached history in his “Mokadima”.This will lead us to the following problematic: At what extent had Ibn-Khaldoun succeeded to develop a new philosophical comprehension of history.